Short Term Outcome of Off Pump Coronary Artery Bypass Grafting in Patients with Low Ejection Fraction (University Heart Journal, 2019)
Coronary artery disease is increasing in developing countries. Revascularization surgery in such patients with amenable coronary anatomy is a valid option. Coronary artery bypass grafting in patients with low ejection fraction (EF